Daya Saing, Spesialisasi, dan Kinerja Ekspor Minyak Atsiri Indonesia di Pasar Internasional - Tampubolon, Yunita Angela; Yuliawati, Yuliawati (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2025)
Indonesia is one of the world's essential oil exporters, with high demand from the perfume, cosmetics, pharmaceutical, food, and beverage industries. However, essential oil exports have fluctuated in five destination countries, namely: Singapore, Spain, the Netherlands, Switzerland, and Germany. This study analyzes Indonesia's competitiveness, trade specialization, and essential oil export performance using Revealed Comparative Advantage (RCA), Export Product Dynamic (EPD), Export Competitiveness Index (ECI), Trade Specialization Index (ISP), Comparative Export Performance (CEP), and Acceleration Ratio (AR) based on UN Comtrade 2014–2023 data with HS code 3301. The results show that Indonesia has a comparative advantage with an average RCA value of 3.53. EPD analysis shows that Germany, the Netherlands, Singapore and Spain are in the Retreat category and Switzerland in the Lost Opportunity category, while the fluctuating ECI indicates unstable competitiveness. ISP confirms Indonesia's position as an essential oil exporter. CEP shows that Indonesia has a relative export advantage over the world average. And AR shows the fluctuating dynamics of export acceleration. To improve competitiveness, product diversification, quality improvement, and more aggressive marketing strategies are needed.